Comparison of Tobramycin, Gentamicin, Colistin, and Carbenicillin in Pseudomonas Sepsis in Monkeys - Saslaw, Samuel (1972)
Intravenous inoculation of 3.4 × 10(10) to 7.4 × 10(10)Pseudomonas aeruginosa organisms into rhesus monkeys 4 days after intravenous or intratracheal inoculation of 2.0 to 2.5 mg of vincristine sulfate resulted in fatal sepsis in eight of nine monkeys. After intramuscular administration, in two equal doses, of 5 mg of tobramycin, gentamicin, and colistin per kg per day beginning 16 hr after challenge, 4 of 11, 4 of 11, and 3 of 10 monkeys died, respectively. Administration of daily doses of 100 to 400 mg of carbenicillin per kg was followed by death in 5 of 12. Duration of illness in the surviving monkeys in each therapy group was similar. Under the conditions of this study, prior administration of vincristine sulfate resulted in a decrease in leukocytes and enhanced susceptibility to Pseudomonas infection. Using this model for studies of comparative efficacy of antibiotics, we observed comparable results after treatment with tobramycin, gentamicin, colistin, and carbenicillin.